Analisa Faktor Yang Mempengaruhi Financial Sustainability Ratio Emiten Perbankan Di BEI Periode 2022-2024 - Juan Carlos Pangestu; Nataherwin Nataherwin; Meyliana Meyliana (Politeknik Ganesha Medan, 2026)
The stability of the banking sector has increasingly become a critical concern as a fundamental pillar in sustaining national economic growth. Financial Sustainability is an essential aspect for banks to assess their potential going concern in the future. This study aims to examine and analyze the effect of Operating Expenses to Operating Income (BOPO), firm size, Return on Assets (ROA), and Loan to Deposit Ratio (LDR) on the Financial Sustainability Ratio (FSR). The population of this study consists of banking sector companies listed in IDX-IC during the period 2022–2024. The sampling technique used is purposive sampling, resulting in 75 financial statement samples. This study employs a quantitative method using secondary data in the form of annual financial reports. Multiple linear regression analysis is applied in the data analysis process. The testing procedures have also met classical assumption tests and the F-test. The results indicate that firm size and Loan to Deposit Ratio have a significant effect on the Financial Sustainability Ratio, while Return on Assets and BOPO do not have a significant effect on FSR. Simultaneously, all variables in this study have a significant effect on FSR. Banking sector companies are expected to pay closer attention to the proportion of their assets and liabilities, as these components significantly influence the level of Financial Sustainability Ratio. Future research is recommended to incorporate non-financial factors such as the board of directors and audit committees, which may also affect the Financial Sustainability of banking firms.